Influence of aromatase inhibitors therapy on the occurrence of rheumatoid arthritis in women with breast cancer: results from a large population-based study of the Italian Society for Rheumatology - Caprioli, Marta (RMD Open, 2017)
OBJECTIVES: The purpose of this study was to evaluate the risk of developing rheumatoid arthritis (RA) in a population of patients with breast cancer treated with aromatase inhibitors (AIs) compared with tamoxifen. METHODS: Data were collected from the administrative healthcare database of Lombardy Region, Italy, from 2004 to 2013. This study follows a nested cohort design, including women with a diagnosis of breast cancer starting treatment with tamoxifen, anastrozole, exemestane or letrozole. The risk of RA related to the prescription of the different drugs was estimated by survival models for competing risks and the results are presented as hazard ratios (HRs) and 95% confidence intervals (95% CI), adjusted for age and cancer severity. RESULTS: Out of total 10 493 women with breast cancer with a median (IQR) age of 66 (57–74), 7533 (71.8%) started an active treatment with AIs or tamoxifen. In this subgroup a total of 113 new cases of RA developed during the 26 105.9 person-year of 10 186 exposure periods, including time varying exposures in the same patient. Using tamoxifen as reference category, AIs therapy was associated with an increased risk of RA (adjusted HR 1.62 (95%1.03–2.56)), in particular in patients receiving anastrozole, even after adjusting for age and level of neoplasia: (adjusted HR 1.75 (95%1.07–2.86)). CONCLUSIONS: In a large population-based sample of women with breast cancer, exposure to AIs compared with tamoxifen is associated with a significantly increased risk of RA, which is not influenced by the cancer severity and the relationship of age with indication to specific drugs.